PENGEMBANGAN BAHAN BELAJAR PENDIDIKAN JASMANI PADA MATERI LARI UNTUK SISWA SEKOLAH DASAR - Mirza Mirza; Imraan Fadhil (Jurnal Dedikasi Pendidikan, 2021)
Educational development must first understand the basic functions of education. able to function education properly. Penjasorkes is one of the lessons that teaches various sports, one of which is athletics, the number of running material. This type of research is research and development, in accordance with the formulation of problems and objectives to be achieved by researchers, namely the development of PJOK learning materials on running material in SD 4 Pidie Jaya packaged in textbooks. Based on the reliability results above, it turns out that all the items are reliable, so that the running material teaching material consists of three preparation materials, namely from design, content and media, each of which has 15 statement items, the first the design has 15 statement items, the second content has 15 statement items, and the third medium has 15 statement items. All items are valid above 0.030. While the reliability test using the Space Saver formula shows that the three forms of running material teaching materials have a reliability coefficient of α 0.393 to 0.727, thus meaning that the three forms of running material, expert validation as teaching materials for running materials for elementary school students, meet the requirements. testing means that the running material teaching materials will provide reliability results that can be trusted and relied on.